Mechanism of Poly(vinyl pyrrolidone) in the Stabilization of Silver Particles - Sophia, J.; Muralidharan*, G. (Asian Journal of Chemistry, 2013)
Silver particles were prepared by chemical reduction method using sodium borohydride (NaBH4) as a reducing agent. The synthesized particles were introduced into the poly(vinyl pyrrolidone) (PVP) polymer, which acted as a stabilizer for silver particles. The resulting collidal solution was characterized using UV-Visible (UV-Vis) spectroscopy which confirmed the presence of silver particles through the characteristic plasmon peak around 400 nm. X-Ray diffraction (XRD) analysis also corroborated the formation of metallic silver particles. The stability of silver particles with and without poly(vinyl pyrrolidone) polymer was compared using UV-visible spectroscopy and scanning electron microscopy (SEM) studies. Silver particles protected by polymer showed better stability than the unprotected metal colloid. Additionally, several other roles of poly(vinyl pyrrolidone) on silver particles were discussed.